PENGGUNAAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER STRUCTURE UNTUK MENINGKATKAN HASIL BELAJAR MATA KULIAH HUKUM ACARA PERDATA PADA MAHASISWA PRODI PPKN FKIP UNIVERSITAS RIAU - Zahirman, Zahirman; Haryono, Haryono; Separen, Separen (Pelita Bangsa Pelestari Pancasila, 2018)
This research aims to improve student results PPKn FKIP UR in the course of civil law, which is the subject of this research is the students of PPKn FKIP UR Semester III totaling 35 people composed of 11 men and 24 women. Process improvements in the research study will use a learning model Numbered Heads Together Structure to see its influence on learning outcomes. Activity faculty and students in the use of this model will be assessed by the observer. Based on the results of the study showed that the activity of a lecturer in the first cycle with a score of 32 categories of